Risk of psychiatric disorders following pelvic inflammatory disease: a nationwide population-based retrospective cohort study. (2nd January 2016) - Shen, Cheng-Che; Yang, Albert C.; Hung, Jeng-Hsiu; Hu, Li-Yu; Chiang, Yung-Yen; Tsai, Shih-Jen
Abstract: Pelvic inflammatory disease (PID) a common infection in women that is associated with significant morbidity and is a major cause of infertility. A clear temporal causal relationship between PID and psychiatric disorders has not been well established. We used a nationwide population-based retrospective cohort study to explore the relationship between PID and the subsequent development of psychiatric disorders. We identified subjects who were newly diagnosed with PID between 1 January 2000 and 31 December 2002 in the Taiwan National Health Insurance Research Database. A comparison cohort was constructed for patients without PID. A total of 21 930 PID and 21 930 matched control patients were observed until diagnosed with psychiatric disorders, or until death, withdrawal from the NHI system, or until 31 December 2009. Adjusted hazard ratio (HR) of bipolar disorder, depressive disorder, anxiety disorder and sleep disorder in subjects with PID were significantly higher (HR: 2.671, 2.173, 2.006 and 2.251, respectively) than that of the controls during the follow-up. PID may increase the risk of subsequent newly diagnosed bipolar disorder, depressive disorder, anxiety disorder and sleep disorder, which will impair life quality. Our findings highlight that clinicians should pay particular attention to psychiatric comorbidities in PID patients.